2012
DOI: 10.1007/s00210-011-0705-z
|View full text |Cite
|
Sign up to set email alerts
|

Gαi2 signaling: friend or foe in cardiac injury and heart failure?

Abstract: Receptors coupled to G proteins have many effects on the heart. Enhanced signaling by Gαs and Gαq leads to cardiac injury and heart failure, while Gαi2 signaling in cardiac myocytes can protect against ischemic injury and β-adrenergic-induced heart failure. We asked whether enhanced Gαi2 signaling in mice could protect against heart failure using a point mutation in Gαi2 (G184S), which prevents negative regulation by regulators of G protein signaling. Contrary to our expectation, it worsened effects of a genet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 37 publications
0
14
0
Order By: Relevance
“…However, if this holds true in actual cardiomyocytes in vivo , it might be part of the mechanism for this β-blocker`s cardio-protective effects. However, several studies do not lend support to this notion; sustained β 1 AR activation by catecholamines, markedly more potent activators of β-arrestin-dependent ERKs in the heart than carvedilol, increases cardiac adverse remodeling even in the absence of cardiac injury[26]. Moreover, carvedilol is also a β 2 - and α 1 AR antagonist, which may interfere with its β-arrestin-activating properties in the heart[27].…”
Section: Functional Differences Between the Two Beta Arrestins In Carmentioning
confidence: 99%
“…However, if this holds true in actual cardiomyocytes in vivo , it might be part of the mechanism for this β-blocker`s cardio-protective effects. However, several studies do not lend support to this notion; sustained β 1 AR activation by catecholamines, markedly more potent activators of β-arrestin-dependent ERKs in the heart than carvedilol, increases cardiac adverse remodeling even in the absence of cardiac injury[26]. Moreover, carvedilol is also a β 2 - and α 1 AR antagonist, which may interfere with its β-arrestin-activating properties in the heart[27].…”
Section: Functional Differences Between the Two Beta Arrestins In Carmentioning
confidence: 99%
“…On the other hand, β 2 AR is thought to confer cardioprotection (38,42). This prosurvival phenotype is thought to be at least in part associated with its interaction with G i proteins (43). In human end stage heart failure patients, G i proteins, particularly the α-2 subunit (G 1α-2 ), are up-regulated (44).…”
Section: The Contribution Of Mir-30 and The β-Adrenergic Pathway Towamentioning
confidence: 99%
“…Activation of G 1α-2 is slightly more controversial as one group demonstrated that constitutive activation of G 1α-2 in a dilated cardiomyopathy and an isoproterenolinduced heart failure mouse model led to worsening hypertrophy and fibrosis, respectively. The authors postulate that the role of G 1α-2 in fibroblasts as opposed to cardiomyocytes may be the driving force behind these phenotypes (43). To complicate the story even more, recent models have demonstrated reverse phenotypes for the role of β 1 AR and β 2 AR in heart failure whereby β 1 AR is cardioprotective and β 2 AR promotes cardiotoxicity (48).…”
Section: The Contribution Of Mir-30 and The β-Adrenergic Pathway Towamentioning
confidence: 99%
“…Most prominently, expression of G iα2 is increased in heart failure (El-Armouche et al 2003). It is controversially discussed whether G iα2 signaling is beneficial or detrimental in heart failure (Kaur et al 2012). Accordingly, the role of G iα2 must be studied in greater detail.…”
mentioning
confidence: 99%